2015
DOI: 10.17957/ijab/15.0022
|View full text |Cite
|
Sign up to set email alerts
|

Triacontanol-induced Regulation in the Key Osmoprotectants and Oxidative Defense System of Sunflower Plants at Various Growth Stages under Salt Stress

Abstract: To cite this paper: Aziz, R. and M. Shahbaz, 2015. Triacontanol-induced regulation in the key osmoprotectants and oxidative defense system of sunflower plants at various growth stages under salt stress. AbstractSalinity is one of the major environmental constraints for limiting crop production at the global level. Exogenous application of triacontanol has the ability to ameliorate the adverse effects of abiotic stresses including salinity stress by modulating a number of physio-biochemical processes in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Physiological effects have been related at the biochemical level to a cellular increase in the content of photosynthetic pigments, soluble sugars, starch, phenols, and proteins 5 , and to stimulation of the activities of carbon and nitrogen metabolism enzymes, such as carbonic anhydrase 5 , 6 , nitrate reductase 6 , ribulose-1,5-bisphosphate carboxylase/oxygenase 7 , and respiratory malate dehydrogenase 8 . More recent studies documented that triacontanol improves the tolerance of plants to abiotic stresses, including salinity 9 , 10 , drought 11 , temperature 12 , and heavy metals 13 , 14 . In general, these studies demonstrated that the improvement of tolerance to stress is due primarily to the increase in the activities of antioxidant enzymes, such as superoxide dismutase, catalase, peroxidase, and those involved in the ascorbate–glutathione cycle 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Physiological effects have been related at the biochemical level to a cellular increase in the content of photosynthetic pigments, soluble sugars, starch, phenols, and proteins 5 , and to stimulation of the activities of carbon and nitrogen metabolism enzymes, such as carbonic anhydrase 5 , 6 , nitrate reductase 6 , ribulose-1,5-bisphosphate carboxylase/oxygenase 7 , and respiratory malate dehydrogenase 8 . More recent studies documented that triacontanol improves the tolerance of plants to abiotic stresses, including salinity 9 , 10 , drought 11 , temperature 12 , and heavy metals 13 , 14 . In general, these studies demonstrated that the improvement of tolerance to stress is due primarily to the increase in the activities of antioxidant enzymes, such as superoxide dismutase, catalase, peroxidase, and those involved in the ascorbate–glutathione cycle 14 .…”
Section: Introductionmentioning
confidence: 99%